المعاهد التقنية العليا بمدينة بنغازي: الواقع والمشكلات - الزليتني سعد محمد (Scientific Journal of University of Benghazi, 2019)
The aim of this study was to understand the present situation of Higher Technical Education in the City of Benghazi and its most pronounced problems and challenges. To achieve this aim descriptive analytical approach was adopted based on case study method. The required data were collected from primary and secondary sources and relevant primary data obtained trough structured interviews conducted with the principals of institutes. Descriptive statistics applied to analyze the collected data. The results show that most institutes suffer from lack of material and human resources and negative impacts of armed conflict, which significantly reduce their overall performance and outputs. However, it s generally observed that technical education, is obtaining acceptance from the people of the city specifically among females as the percentage of female students has reached 46% of the total enrollments. Based on the study results, it is recommended that more attention should be paid to this type of education and provided with necessary capabilities and equipments, and connected with real demands of local economic and social activities.